Methods to managing safe behaviors in the workplace - TELALI, Nabila (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2026)
This research paper derives its importance from the importance of human resources, the changes observed in the field of organizational behavior have not been limited solely to the behavior of individuals within the organization, but have also expanded to include the management of these behaviors. One of the key functions that organizations now focus on in managing behaviors is the management of safe behaviors in the workplace, aiming to prevent and avoid work-related accidents and the associated individual and organizational problems. This also involves effecting changes in skills, expertise, and methods for safe and effective work practices. Every organization bases its principles Logo of the French Ergonomic Society: "When we are at our best and in a good position, we are the strongest." This reflects the commitment of organizations to activate safety procedures and behaviors, provide protective equipment, and meet all necessary requirements to avoid work accidents. This includes the individual's awareness of correct actions and dangerous behaviors that may lead to occupational problems, including injuries or occupational diseases. Using a descriptive approach, the research paper addressed the most important basic approaches to managing safe behaviors in the workplace. It also addressed the most important steps taken by management and employees alike to avoid occupational accidents or exposure to diseases that may affect them. It analyzed each approach and the training and field steps it requires, which must be acquired and implemented. A comparison was also made between these approaches and the benefits they offer, supporting the topic with previous studies and proposing a comprehensive, integrated approach to managing occupational health and safety in the workplace. To explore and describe these approaches, we can pose the following questions: What are safe behaviors in the workplace? What are the safe requirements to avoid occupational accidents?